Frauds in the Indian Banking Industry: Concerns and Cures - Kumar Purbey, Dr. Uttam (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
The Indian banking sector has experienced considerable growth and changes since liberalisation of economy in 1991. Though the banking industry is generally well regulated and supervised, the sector suffers from its own set of challenges when it comes to ethical practices, financial distress and corporate governance. This study endeavour to cover issues such as banking frauds and mounting credit card debt, with a detailed analysis using secondary data (literature review and case approach) as well as an interview-based approach, spanning across all players involved in reporting financial misconduct. The report touches upon the case of rising NPAs in the past few years across various scheduled commercial banks, especially public-sector banks. The study finally proposes some recommendations to reduce future occurrence of frauds in Indian banking sector. The credibility of third parties such as auditing firms and credit rating agencies is also questioned in the study and is believed to be a significant contributor amongst other causes, such as oversight by banks and inadequate diligence. KEYWORDS: Non-performing assets, Stressed assets, Banking frauds, Financial Misconduct